Obtainingvaccinia virus with increased production of extracellular enveloped virions and directing GM-CSF synthesis as a promising basis for development of antitumor drug - T. V. Bauer; T. V. Tregubchak; S. N. Shchelkunov; R. A. Maksyutov; E. V. Gavrilova (Медицинская иммунология, 2020)
The problems of oncological disease treatment are considered relevant and timely issues of the current research programs. Since monotherapy is increasingly clear to be less effective than combination therapy, the novel studies seek for advancement of current treatments and development of new ones employing oncolytic immunotherapy being among the most rapidly evolving approaches. Modern genetic engineering techniques enable new applications of oncolytic viruses in the frames of combined cancer therapy. These applications are feasible, due to the abilities of oncolytic viruses to destruct tumor cells, like as by changing susceptibility of cancer cells to anti-tumor drug, and upon the whole body, thus overcoming the mechanisms conferring immunoresistance of tumor cells. In the present work, we have developed a recombinant vaccinia virus which is a promising platform for designing the antitumor drugs. The following modifications of viral genome were made by means of genetic engineering: gene encoding granulocyte-macrophage colony-stimulating factor was inserted into the region of viral thymidine kinase gene; viral A34R gene encoding a membrane glycoprotein, was replaced by A34R gene with two nucleotide substitutions resulting into D110N and K151E mutations which cause increased proportion of extracellular enveloped virions during the virus reproduction. Some properties of the recombinant virus were studied in vitro. The virus was shown to produce granulocyte-macrophage colony stimulating factor, and high numbers of extracellular enveloped virions. The genome modifications had no effect upon viral replication.